2022
DOI: 10.1136/jclinpath-2022-208215
|View full text |Cite
|
Sign up to set email alerts
|

Update regarding the role of PD-L1 in oncocytic thyroid lesions on cytological samples

Abstract: AimsSeveral papers have shown that programmed death-ligand 1 (PD-L1) expression is a relevant predictive biomarker in anti-PD-L1 cancer immunotherapy. While its role in several human cancers is correlated with poor prognosis and resistance to anticancer therapies, in thyroid cancers the role of PD-L1 remains questionable. Few articles have studied PD-L1 in thyroid fine-needle aspiration cytology (FNAC), demonstrating a possible correlation with papillary thyroid carcinoma. However, its role in oncocytic thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…This confirmed the adverse effects of PD-L1 positivity and leading to it being considered a risk factor for long-term recurrence (24). Previous research on the effect of PD-L1 in PTC mainly focused on clinical and histopathological manifestations (25)(26)(27), while the relationship between PD-L1 and ultrasound and study on the joint effect of the two on thyroid cancer prognosis were seldom reported. Our work examined whether PD-L1 was associated with ultrasonic characteristics.…”
Section: Discussionmentioning
confidence: 53%
“…This confirmed the adverse effects of PD-L1 positivity and leading to it being considered a risk factor for long-term recurrence (24). Previous research on the effect of PD-L1 in PTC mainly focused on clinical and histopathological manifestations (25)(26)(27), while the relationship between PD-L1 and ultrasound and study on the joint effect of the two on thyroid cancer prognosis were seldom reported. Our work examined whether PD-L1 was associated with ultrasonic characteristics.…”
Section: Discussionmentioning
confidence: 53%